Facilitating the dry reforming of methane with interfacial synergistic catalysis in an Ir@CeO2−x catalyst - Hui Wang; Guoqing Cui; Hao Lu; Zeyang Li; Lei Wang; Hao Meng; Jiong Li; Hong Yan; Yusen Yang; Min Wei (Nature Communications, 2024)
Abstract The dry reforming of methane provides an attractive route to convert greenhouse gases (CH4 and CO2) into valuable syngas, so as to resolve the carbon cycle and environmental issues. However, the development of high-performance catalysts remains a huge challenge. Herein, we report a 0.6% Ir/CeO2−x catalyst with a metal-support interface structure which exhibits high CH4 (~72%) and CO2 (~82%) conversion and a CH4 reaction rate of ~973 μmolCH4 gcat −1 s−1 which is stable over 100 h at 700 °C. The performance of the catalyst is close to the state-of-the-art in this area of research. A combination of in situ spectroscopic characterization and theoretical calculations highlight the importance of the interfacial structure as an intrinsic active center to facilitate the CH4 dissociation (the rate-determining step) and the CH2* oxidation to CH2O* without coke formation, which accounts for the long-term stability. The catalyst in this work has a potential application prospect in the field of high-value utilization of carbon resources.